Desert Dust as a Source of Iron to the Globally Important Diazotroph Trichodesmium - Polyviou, Despo; Baylay, Alison J.; Hitchcock, Andrew; Robidart, Julie; Moore, C. M.; Bibby, Thomas S. (Frontiers in Microbiology, 2018)
The marine cyanobacterium Trichodesmium sp. accounts for approximately half of the annual ‘new’ nitrogen introduced to the global ocean but its biogeography and activity is often limited by the availability of iron (Fe). A major source of Fe to the open ocean is Aeolian dust deposition in which Fe is largely comprised of particles with reduced bioavailability over soluble forms of Fe. We report that Trichodesmium erythraeum IMS101 has improved growth rate and photosynthetic physiology and down-regulates Fe-stress biomarker genes when cells are grown in the direct vicinity of, rather than physically separated from, Saharan dust particles as the sole source of Fe. These findings suggest that availability of non-soluble forms of dust-associated Fe may depend on cell contact. Transcriptomic analysis further reveals unique profiles of gene expression in all tested conditions, implying that Trichodesmium has distinct molecular signatures related to acquisition of Fe from different sources. Trichodesmium thus appears to be capable of employing specific mechanisms in accessing Fe from complex sources in oceanic systems, helping to explain its role as a key microbe in global biogeochemical cycles.